THE RELATIONSHIP BETWEEN PARENTING STYLES AND ACADEMIC SELF-ESTEEM AMONG PRESCHOOL CHILDREN IN SABANG - Salmiati (Department of Early Childhood Education, STKIP Bina Bangsa Getsempena, 2015)
Parenting styles play an important role in child development. Extensive studies have been conducted concerning on the relationship between parenting styles and adolescents’ self-esteem. However, the studies focusing on the relationship between parenting styles and preschool children’s academic self-esteem are highly limited. Hence, this study observed the relationship between parenting styles and self-esteem among preschool children’s in Sabang. A total of 107 preschool children’s parents completed the Parenting Style Dimensional Questionnaires (PSDQ) and their children were observed by teachers using Behavioral Academic Self-Esteem (BASE). The result showed that authoritative parenting style was predominantly practiced by parents and most children displayed moderate academic self-esteem. A significant relationship was found between authoritarian and academic self-esteem (r = -.461, p < .05). In addition, a significant correlation was also found between authoritative parenting style and academic self-esteem (r .348, p < .05), while there was no significant relationship between permissive parenting style and academic self-esteem (r = .000, p > .000). The findings indicated that there were no differences in academic self-esteem among male students (M= 1.85, SD= .583, n = 48) and female students (M= 2.10, SD= .51, n = 59) and t (-. 2300 (95) p < .05. The implications and suggestions will also be discussed in the light of finding.